1970
DOI: 10.1071/ea9700237
|View full text |Cite
|
Sign up to set email alerts
|

Potassium permanganate as an ethylene absorbent in polyethylene bags to delay ripening of bananas during storage

Abstract: Potassium permanganate reduced the concentration of ethylene and calcium hydroxide reduced the concentration of carbon dioxide in sealed polyethylene bags containing bananas. When the fruit that were not packed in sealed bags were ripe (16 days after the beginning of storage) all the fruit in sealed polyethylene bags were in a firm green condition and there was little difference between treatments in sealed polyethylene bags. After 29 days some of the fruit in sealed bags had softened, but fruit in bags contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 8 publications
3
30
0
Order By: Relevance
“…In turn, the rate of respiration results from the interaction of the genetic nature of the produce, its physiological status, temperature and the influence of ethylene, oxygen and carbon dioxide concentrations (Kays, 1997;Wills et al, 1998). A storage life similar to that of fruit held under refrigeration can be achieved at ambient temperature by packing fruit within sealed polyethylene bags, especially with ethylene absorbents such as potassium permanganate (Scott, McGlasson & Roberts, 1970;Chaplin, 1989;Ketsa, Raksritong & Subhadrabandhu, 1992;Ben-Yehoshua et al, 1996;Leena et al, 1997). However, the general usefulness of sealed plastic bags with scrubbers is limited because high temperature can act to adversely influence fruit quality and shelf life through CO 2 levels becoming too high and/or O 2 levels going too low (Kader et al, 1989;Banks, Cleland, Yearsley & Kingsley, 1993;Koolpluksee, Ketsa & Subhadrabandhu, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the rate of respiration results from the interaction of the genetic nature of the produce, its physiological status, temperature and the influence of ethylene, oxygen and carbon dioxide concentrations (Kays, 1997;Wills et al, 1998). A storage life similar to that of fruit held under refrigeration can be achieved at ambient temperature by packing fruit within sealed polyethylene bags, especially with ethylene absorbents such as potassium permanganate (Scott, McGlasson & Roberts, 1970;Chaplin, 1989;Ketsa, Raksritong & Subhadrabandhu, 1992;Ben-Yehoshua et al, 1996;Leena et al, 1997). However, the general usefulness of sealed plastic bags with scrubbers is limited because high temperature can act to adversely influence fruit quality and shelf life through CO 2 levels becoming too high and/or O 2 levels going too low (Kader et al, 1989;Banks, Cleland, Yearsley & Kingsley, 1993;Koolpluksee, Ketsa & Subhadrabandhu, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Transport of the fruit to the laboratory at ambient temperature (15--20 ° C) required another 20 h. On arrival, treatment groups of five replicate fruit were stored in constant-temperature rooms held at 20 and 30°C for 0 (control), 4, 6, 8 and 11 days to simulate a range of postharvest transportation regimes. At the end of each storage period, the gas composition inside the bags was determined by gas chromatography (Scott et al, 1970). The fruit were then transferred to individual gas-tight respiration jars (1.25 1) ventilated with a constant flow of C2H4-free air at 20 ° C, and allowed to ripen.…”
Section: Controlled Temperature Storage -~ Experiments Imentioning
confidence: 99%
“…The ability of potassium permanganate in reducing the ethylene concentration in the atmosphere around horticultural produce was first demonstrated by Forsyth et al (1967) in apples. It was demonstrated that KMnO 4 retarded the ripening of many fruits (Scott et al 1970;Wills et al 1989).…”
Section: Introductionmentioning
confidence: 99%